The Rhizobium-Legume Symbiosis: Co-opting Successful Stress Management - Hawkins, Justin P.; Oresnik, Ivan J. (Frontiers in Plant Science, 2022)
The interaction of bacteria with plants can result in either a positive, negative, or neutral association. The Rhizobium-Legume interaction is a well-studied model system of a process that is considered a positive interaction. This process has evolved to require a complex signal exchange between the host and the symbiont. During this process, rhizobia are subject to several stresses, including low pH, oxidative stress, osmotic stress, as well as growth inhibiting plant peptides. A great deal of work has been carried out to characterize the bacterial response to these stresses. Many of the responses to stress are also observed to have key roles in symbiotic signalling. We propose that stress tolerance responses have been co-opted by the plant and bacterial partners to play a role in the complex signal exchange that occurs between rhizobia and legumes to establish functional symbiosis. This review will cover how rhizobia tolerate stresses, and how these tolerance mechanisms play a role in signal exchange between rhizobia and legumes.